Pelatihan Penyusunan Biaya Operasional Penyelenggaraan PAUD di Kelurahan Cisaranten Kidul Kecamatan Gedebage Kota Bandung - Kurniadi, Budi; Susanti, Dian (Jurnal Pengabdian Tri Bhakti, 2020)
Early Childhood Education (PAUD) a kind of PAUD Unit (SPS) one of form of organization early which focuses on basic placement in the direction of physical growwth and development (fine and gross motor coordination), intelligence (power of thought, creativity, emotional intelligent, spiritual intelligent), socio emotional (attitudes and behavior and variety), language and communication, in accordance with the uniqueness and the stages of development that are traversed by the children. Meanwhile the high demans of teachers as a consequnce of the issueance of ministerial regulations empowering the state apparatus and bureaucratic reform (goverment regulations) number 16 year 2009 about funtional positions and creadit scoure. The approach method used to improve the quality of services provided by educators and education staff in carrying out early childhood education services is to provide training in the provision of PAUD in general. In addition to providing training the method used is mentoring, with this method after partners can feel the benefits of training assistance optimally, partners are also expected to carry out their duties proper. The target for the implementation of the paud organizer program is to provide assistance in preparing reports on government assistance through non-physical BOP grants (operational operational costs) for the paud can be optimally ranging from planning, preparation to management of PAUD management. Thus PAUD organizers can better understand and plan in managing early education institutions in their own environment so that ultimately it will improve the quality of education services.